Rebirth According to the Bhagavad gītā; Epistemology, Ontology and Ethics - Ithamar Theodor (Religions, 2017)
This paper is engaged with the topic of reincarnation in the Bhagavad gītā, better termed “rebirth”. It first looks into the epistemological aspects of rebirth, and highlights the type of knowledge or terminology underlying the vision of rebirth, as opposed to a different type of knowledge that is not suitable for this purpose, and which leads to a different vision of reality. It then looks into the ontological aspects of rebirth, and having highlighted some Upaniṣadic sources, it highlights major Bhagavad gītā sections describing the soul and rebirth. Finally, it looks into the ethics derived from the concept of rebirth; it first characterizes these as “ethics of equanimity”, and then expands these into the “ethics of enlightened action”, which refer to action grounded in the idea of rebirth.